The environmental pathway: A scoping review on fiscal-financial synergy for sustainable county development - Mujie Zhao; Jianqi Song (Environment and Social Psychology, 2025)
A critical gap persists in the sustainability literature regarding the integrated transmission pathway from fiscal-financial policy synergy to regional development, where the environment’s role as a key mediator remains under-theorized and the underlying micro-behavioral mechanisms are largely overlooked. This scoping review addresses this gap by constructing a “policy-environment-development” mediation framework, theoretically grounded in the Theory of Planned Behavior (TPB). Our analysis demonstrates that green fiscal and financial instruments enhance a region’s adaptive, restorative, and transformative capacities by improving ecological quality. This environmental pathway functions by strategically shaping the behavioral intentions of key actors: influencing attitudes through incentives, forging subjective norms via market signals, and enhancing perceived behavioral control by alleviating constraints. To enable the rigorous application and evaluation of this framework, our synthesis underscores the critical need to advance standardized environmental value accounting. Such a system is essential to robustly quantify the environment’s contribution to economic development, thereby providing a universal metric for assessing policy effectiveness. The primary theoretical contribution of this study is the integration of separated research strands into a coherent model that clarifies the environmental mediation process, establishes its micro-behavioral foundations, and charts a path for its empirical validation through integrated behavioral and environmental measurement.